Inhibition of phospholipase D promotes neurological function recovery and reduces neuroinflammation after spinal cord injury in mice - Ke, Han; Bai, Fan; Li, Zihan; Zhu, Yanbing; Zhang, Chunjia; Li, Yan; Talifu, Zuliyaer; Pan, Yunzhu; Liu, Wubo; Xu, Xin; Gao, Feng; Yang, Degang; et al. (Frontiers in Cellular Neuroscience, 2024)
Spinal cord injury (SCI) is a severely disabling disease. Hyperactivation of neuroinflammation is one of the main pathophysiological features of secondary SCI, with phospholipid metabolism playing an important role in regulating inflammation. Phospholipase D (PLD), a critical lipid-signaling molecule, is known to be involved in various physiological processes, including the regulation of inflammation. Despite this knowledge, the specific role of PLD in SCI remains unclear. In this study, we constructed mouse models of SCI and administered PLD inhibitor (FIPI) treatment to investigate the efficacy of PLD. Additionally, transcriptome sequencing and protein microarray analysis of spinal cord tissues were conducted to further elucidate its mechanism of action. The results showed that PLD expression increased after SCI, and inhibition of PLD significantly improved the locomotor ability, reduced glial scarring, and decreased the damage of spinal cord tissues in mice with SCI. Transcriptome sequencing analysis showed that inhibition of PLD altered gene expression in inflammation regulation. Subsequently, the protein microarray analysis of spinal cord tissues revealed variations in numerous inflammatory factors. Biosignature analysis pointed to an association with immunity, thus confirming the results obtained from transcriptome sequencing. Collectively, these observations furnish compelling evidence supporting the anti-inflammatory effect of FIPI in the context of SCI, while also offering important insights into the PLD function which may be a potential therapeutic target for SCI.